Fluorescent recognition of uranyl ions by a phosphorylated cyclic peptide1. Issue 59 (28th July 2015) - Yang, Chu-Ting; Han, Jun; Gu, Mei; Liu, Jun; Li, Yi; Huang, Zeng; Yu, Hai-Zhu; Hu, Sheng; Wang, Xiaolin
<x xml:space="preserve">Abstract</x> Fluorescent recognition of uranyl ions was achieved using a phosphorylated cyclic peptide, which can be used as a fluorescent sensor.